Comparison of electrical bioimpedance in newborns with electrodes positioned on the right and left sides of the body - Thatyana Ribeiro Medeiros; Camila Barros Melgaço da Silva; Flávia Nunes Benicio de Souza; Hannah Schmidel Kautsky; Luana Martins de Oliveira; Luana Martins de Toledo; Alan Araújo Vieira (Jornal de Pediatria)
Objective: Bioelectrical impedance analysis is a method used to assess body composition; a noninvasive test performed using an easy-to-handle portable device used in clinical practice. However, nonstandard methods in neonates hinder external validation and reliability. Currently, bioimpedance analysis is performed in newborns with electrodes positioned on the right side of the body; however, the use of medical devices, including vascular access, can prevent its use. Methods: An uncontrolled before-after clinical trial comparing resistance and reactance measurements by bioelectrical impedance analysis on both sides was conducted. Measurements were performed immediately after the randomization of the initial measurement side. The sample size was calculated by considering a 10% deviation from the mean resistance and reactance values of previous studies with alpha and beta errors of 10% and 20%, respectively. Binary linear regression was used to quantify the correlation. Results: A significant difference was observed between resistance (672.88 ± 136.30 vs. 649.22 ± 119.59) and reactance (46.34 ± 17.99 vs. 44.439 ± 19.42) values measured on the right and left sides, respectively. However, when measured on both sides of the body, resistance and reactance values showed a good correlation (0.98 for both models, p < 0.001). Positioning the electrodes on the left side significantly affected the resistance and reactance values measured by bioelectrical impedance analysis compared with those on the right side. Conclusion: Electrodes positioned on opposite sides of the body generated different resistance and reactance values, implying the need to use the right side exclusively for standard positioning. This restriction can create difficulties for the routine use of this technique in newborns.